Pengaruh Media Sosial Sebagai Sumber Pengetahuan Politik Generasi Z Terhadap Literasi Politik Pada Pemilu 2020 - Aziz, Abdhul; Widodo, Bambang (Universitas Muhammadiyah Yogyakarta, 2022)
Pilkada is a process of implementing democracy that is followed by all circles of society, including generation Z. Social Media is very closely related to Generation Z. Generation Z tends to master technology and the internet since childhood. In the implementation of the 2020 Pilkada. Therefore, it is necessary to study the influence of social media as a source of political knowledge on political literacy in the 2020 Election of Blora Regency in the era of the covid-19 pandemic. This study aims to determine how influential social media is as a source of political knowledge in political literacy generation Z. This study was designed using mixed methods with a sequential explanatory strategy with data collection and quantitative data analysis in the first stage, followed by qualitative data collection and analysis. The sample in this study is Generation Z aged 17-24 years in Blora Regency, who have used their voting rights in the 2020 Pilkada. This study indicates that generation Z's political knowledge, knowledge of government, and knowledge of the environment and society are considered sufficient for political literacy. Because it is in the 2,3-3.6 interval, knowledge related to the political game rules is considered suitable for political literacy because it is at the highest interval of 3.6-4.9. From the output, the R square of political knowledge has a value of 0.641, which means that 64.1% of generation Z's political knowledge affects political literacy. Social media as a source of political knowledge affects the level of political literacy of generation Z. Other factors that can influence the political knowledge of generation Z are age, education, sources of information, experience, and occupation. However, social media as a source of political knowledge has not been appropriately utilized by the organizers and the candidate pair in providing information to voters.